QUANTITY AND QUALITY OF INFORMATION, EDUCATION AND COMMUNICATION DURING ANTENATAL VISIT AT PRIVATE AND PUBLIC SECTOR HOSPITALS OF BAHAWALPUR, PAKISTAN - Mahar, Benazeer; Kumar, Ramesh; Rizvi, Narjis; Bahalkani, Habib Akhtar; Haq, Mahboobul; Soomro, Jamila (Journal of Ayub Medical College Abbottabad, 2012)
Background: Information, education and communication (IEC) by health care provider to pregnant woman during the antenatal visit are very crucial for healthier outcome of pregnancy. This study analysed the quality and quantity of antenatal visit at a private and a public hospital of Bahawalpur, Pakistan. Methods: An exit interview was conducted from 216 pregnant women by using validated, reliable and pre-tested adapted questionnaire. First sample was selected by simple random sampling, for rest of the sample selection systematic random sampling was adapted by selecting every 7th women for interview. Ethical considerations were taken. Results: Average communication time among pregnant woman and her healthcare provider was 3 minute in public and 8 minutes in private hospital. IEC mainly focused on diet and nutrition in private (86%) and (53%) public, advice for family planning after delivery was discussed with 13% versus 7% in public and private setting. None of the respondents in both facilities got advice or counselling on breastfeeding and neonatal care. Birth preparedness components were discussed, woman in public and private hospital respectively. In both settings antenatal clients were not received information and education communication according to World Health Organization guidelines. Conclusion: Quality and quantity of IEC during antenatal care was found very poor in both public and private sector hospitals of urban Pakistan. Keywords: Antenatal Care, Public and Private Hospitals, Communication, Information, Education